2006
DOI: 10.1590/s1676-06032006000300001
|View full text |Cite
|
Sign up to set email alerts
|

Growth rings in cerrado woody species: occurrence and anatomical markers

Abstract: Marcati, C.R.; Oliveira, J.S. and Machado, S.R. Growth rings in cerrado woody species: occurrence and anatomical markers. Biota Neotrop. Sep/Dez 2006 vol. 6, no. 3 http://www.biotaneotropica.org.br/v6n3/pt/abstract?article+bn00206032006 ISSN 1676-0611 Growth ring occurrence was investigated in 48 representative species of cerrado in the state of São Paulo, Brazil. We characterized growth ring markers and described the growth layer structure of the basal portion of the most developed stem branches in woody pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
1
6

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 14 publications
2
16
1
6
Order By: Relevance
“…Marcati et al (2006) reported distended rays delimiting growth rings in addition to other markers to some species from cerrado (Piptocarpha rotundifolia (Asteraceae), Annona coriacea and A. crassiflora (Annonaceae)). The distended rays delimiting growth rings might be advantageous in addition to the other growth markers helping the dendrochronologists in the correct distinction of the growth rings limits.…”
Section: Discussionmentioning
confidence: 99%
“…Marcati et al (2006) reported distended rays delimiting growth rings in addition to other markers to some species from cerrado (Piptocarpha rotundifolia (Asteraceae), Annona coriacea and A. crassiflora (Annonaceae)). The distended rays delimiting growth rings might be advantageous in addition to the other growth markers helping the dendrochronologists in the correct distinction of the growth rings limits.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the reduction of cell expansion and growth in W. trihostephia during periods of low water availability, combined with the stable volume of radial parenchyma cells and the consequent cambium inactivity, forms seasonal growth rings. Marcati et al (2006) discussed the occurrence of seasonal growth rings in a variety of different Cerrado species, and concluded that it may be related to a distinct annual dry season; however, this feature is poorly understood for species of the Chaco and deserves further investigation into its adaptive value.…”
Section: Underground System Anatomymentioning
confidence: 99%
“…Na região de estudo, a estação seca estende-se de maio a setembro, com média da precipitação no período de 40,6 a 72,5 mm, o que pode estar provocando a formação de camadas de crescimento no lenho de S. adstringens. Marcati et al (2006), ao analisarem o lenho de 48 espécies lenhosas de cerrado, verificaram que 61% delas possuíam camadas de crescimento bem definidas e 33% apresentaram camadas de crescimento pouco definidas.…”
Section: Figura 2 Figureunclassified